STYLE OF WRITING SCIENTIFIC ARTICLES THESIS POSTGRADUATE STUDENTS OF INDONESIAN LANGUAGE PROGRAM UNIVERSITAS SEBELAS MARET - Susanti, Eka Maria; Setiawan, Budhi; Rohmadi, Muhammad (English Department FBS UNP, 2017)
The style of writing scientific articles published in scientific journals has an important role in the assessment of an article. This study aimed to describe whether the form of writing scientific articles style on Indonesian Education Program students of Universitas Sebelas Maret was in accordance with Accreditation Guidlines of Scientific Parodical Issue (PATBI) published by Ditlitabmas Directorate General of Higher Education. This research is a qualitative descriptive research. The data in this research were two scholarly article documents of master's students thesis of Indonesian Education Program of Universitas Sebelas Maret Surakarta and Guidelines of Accreditation of Scientific Periodic Issue. Data collection technique used in this research was purposive sampling technique. The validity of data used triangulation theory and data analysis technique in this research used interactive analysis model. The results of this study indicated that the thesis scientific article created by postgraduated students of Universitas Sebelas Maret was in accordance with the rules and guidelines for accreditation of periodical publication published by Ditlitabmas Directorate General of Higher Education.Key words/phrases: style of writing, scientific articles, thesis, GAYA PENULISAN ARTIKEL ILMIAH TESIS MAHASISWA PASCASARJANA PENDIDIKAN BAHASA INDONESIA UNIVERSITAS SEBELAS MARETAbstrakBentuk gaya penulisan artikel ilmiah yang diterbitkan dalam jurnal ilmiah memiliki peran yang penting dalam penilaian sebuah artikel. Penelitian ini bertujuan untuk mendeskripsikan bentuk gaya penulisan artikel ilmiah tesis mahasiswa Program Pascasarjana Pendidikan Bahasa Indonesia Universitas Sebelas Maret apakah sesuai dengan Pedoman Akreditasi Terbitan Berkala Ilmiah yang diterbitkan oleh Ditlitabmas Direktorat Jenderal Pendidikan Tinggi. Penelitian ini merupakan penelitian deskriptif kualitatif. Data dalam penelitian ini berupa dua dokumen artikel ilmiah tesis mahasiswa Program Pascasarsana Pendidikan Bahasa Indonesia Universitas Sebelas Maret Surakarta dan Pedoman Akreditasi Terbitan Berkala Ilmiah. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah teknik purposive sampling. Keabsahan data menggunakan triangulasi teori. Teknik analisis data dalam penelitian ini menggunakan model analisis interaktif. Hasil penelitian ini menunjukkan bahwa artikel ilmiah tesis yang dibuat oleh mahasiswa pascasrjana Universitas Sebelas Maret sudah sesuai dengan aturan dan pedoman akreditasi terbitan berkala ilmiah yang diterbitkan oleh Ditlitabmas Dirjen Pendidikan Tinggi. Kata Kunci: gaya penulisan, artikel ilmiah, tesis